Ultra‐high step‐up two‐input DC–DC converter with lower switching losses. Issue 9 (10th July 2019) - Mohseni, Parham; Hossein Hosseini, Seyed; Maalandish, Mohammad; Sabahi, Mehran
Abstract : In this study, a novel isolated ultra‐high step‐up two‐input DC–DC converter with low‐voltage stress across semiconductors is presented. In the proposed converter, outputs are isolated from the inputs by a high‐frequency transformer and the leakage inductance of the transformer is used to soft switching (zero‐current switching) of the power switches when they are turned‐on and alleviate the reverse recovery problems of the diodes. This converter can be operated as an interleaved single‐input converter with a 180° phase shift. The converter benefits from the advantages of both the conventional boost converter and diode‐capacitor voltage multiplier (VM) stages. The primary side of the transformer consists of two‐input cells based on the conventional boost converter and the secondary side consists of diode‐capacitor VM stages which are used to increase the voltage gain and decrease the nominal voltage stress across semiconductors. To confirm the converter performance, the mathematical analysis and simulation result are presented, in addition, the comparison between the proposed converter and other converters which are presented in recent studies is presented. An experimental prototype 410 V/280 W of the converter with 40 and 45 V input voltages is provided to illustrate the correct operation of the presented converter.